Karakterisasi Sistem Dispersi Padat Meloksikam Dengan Matriks PEG 6000 Dan Poloxamer 188 Dibuat Dengan Menggunakan Metode Peleburan - Najih, Yuli Ainun; Nailufa, Yuyun; Rakhma, Dita Nurlita; Widjaja, Bambang; Silviyah, Lailatul; Mujahida, Choirun (Journal of Islamic Pharmacy, 2021)
Meloxicam is included in the class II Biopharmaceutical Classification System (BCS). This drug has low solubility and high permeability. The solubility is one of the factors that affect in the dissolution rate of drug. One of the effort to increase dissolution of meloxicam is by forming a solid dispersion system made using melting method. The addition of PEG 6000 and poloxamer 188 carriers determine in the solid dispersion system aims to increase the dissolution rate of meloxicam. The purpose of this study is to characterize the meloxicam solid dispersion system with PEG 6000 and poloxamer 188 matrices at a ratio of 99:1 and 98:2 made by the melting method when compared with the physical mixture and its pure compound using Powder X-Ray Diffaction, DSC and FTIR. The results of meloxicam solid dispersion with a ratio 99:1 and 98:2 showed the disappearance of the typical peak of meloxicam at an angel of 2θ 6.5° and 11.2°. The thermogram data using DSC shows a decrease in melting point of solid dispersion system with a ratio of 99:1 and 98:2 namely 64.33°C and 64.21°C. The result of the characterization of meloxicam solid dispersion with FTIR showed that the identified spectrum were in the spectrum range of meloxicam, PEG 6000, poloxamer 188 indicating there was no incteraction in the meloxicam solid dispersion system.Keywords: Meloxicam, PEG 6000, Poloxamer 188, Solid Dispersion, Melting Method, Characterization